THE IDEA OF RADICAL FEMINISM IN THE NOVEL “WOMAN AT POINT ZERO” - Az-Zahra, Andi Nurfatimah; Mustikawati, Yunitari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This research aims to the form of radical feminism and how it is resisted in the novel